2013
DOI: 10.2147/oajsm.s41586
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of musculoskeletal disorders among Norwegian female biathlon athletes

Abstract: The purpose was to examine musculoskeletal disorders in Norwegian female biathlon athletes (age ≥ 16), both juniors and seniors. The design was a retrospective cross-sectional study. In all, 148 athletes (79.1%) responded; of these, 118 athletes were 16–21 years (juniors) (77.6%), and 30 athletes were 22 years or older (seniors) (20.3%), and mean age was 19.1. A validated questionnaire was used to collect the data. The prevalence of musculoskeletal disorders was 57.8%. The most affected parts were the knee (23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…First, no detailed questionnaire was used regarding the subject’s history of injury to identify the environment in which the injury occurred. Among skaters, off-ice training is one of the most common precipitating risk factors for injury, 29 and we were unable to precisely evaluate the mechanisms underlying such injuries.…”
Section: Discussionmentioning
confidence: 99%
“…First, no detailed questionnaire was used regarding the subject’s history of injury to identify the environment in which the injury occurred. Among skaters, off-ice training is one of the most common precipitating risk factors for injury, 29 and we were unable to precisely evaluate the mechanisms underlying such injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies conducted to establish the extent of injuries and illness have been retrospective or based on questionnaires; 11 , 18 , 19 however, recall bias associated with retrospective study designs often restricts the interpretation of injury-surveillance studies. As such, a prospective study design should be used to avoid recall biases.…”
Section: Introductionmentioning
confidence: 99%
“…during the year preceding the survey (incidence =586 injuries per 1000 athletes per year). 9 Similar to a study cohort of cross country skiers, 10 female biathletes reported more injuries than males (55% vs 40%). 9 Recognition of the role of illness is growing in sports medicine, for instance, physiological changes associated with acute infective illness impair motor coordination, decrease muscle strength, 11 reduce peak V02 (peak oxygen consumption) and endurance capacity and change metabolic function, 12 consequently affecting biathletes ability to train, compete 2 and perform well.…”
Section: Introductionmentioning
confidence: 57%